PENGARUH PEMBERIAN KUPEDES PT. BANK RAKYAT INDONESIA (Persero) Tbk, UNIT TODDOPULI TERHADAP TINGKAT PENDAPATAN PENGUSAHA KECIL DI MAKASSAR - Badaruddin Badaruddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
As for the purpose of this study is 1). To determine how much influence the provision Kupedes PT. BRI (Persero) Tbk Unit Toddopuli the income levels of small entrepreneurs in Makassar 2). To determine differences in small business income, before obtaining the loan and after obtaining credit. Simultaneously, there is a significant effect between the independent variables Equity (X ₁), Capital Loans (X ₂) to small businesses whose income (Y). This is evident from the calculated F value is large with a significant level 0.000 92 488 less than the alpha value of 0.05. And independent variables (Equity and Equity Loans) indicated a large effect by R = 0.847 or 84.7% of the dependent variable (income level). While the major contribution of the variable to the level of income (Y), which is indicated by the R Square of 0.717 or 71.7%. In other words 71.7% rate pendapata (Y) is influenced by the independent variables (X1 and X2), while the remaining 28.3% were caused by other factors that are not taken into account in this variable. Partially or individually, there are two independent variables that significantly influence the level of small business income, based on the analysis conducted after a change in income customers receive a credit of 9.98% of previous income. Operating revenues average respondent before receiving loans amounting to Rp 1,554,958. While businesses operating revenues average respondent after receiving loans of Rp 15,614,703. From the calculation of the variable t own capital, from the data obtained indicated that t count> t table or 12.804> 1.992 with a significant level (α) of 0.000 <0.05, as well as lending capital variables, ditujunkkan of the data obtained is t count> t table or 2.097> 1.992 with a significant level (α) of 0.039 <0.05. Thus it can be said that the number of small business income before getting a loan and after getting a loan from BRI indicate a significant difference. With the PT BRI (Persero) Unit Toddopuli considered to have a positive impact on small businesses in improving their business.